INTEGRATING AI IN LANGUAGE LEARNING: A CASE STUDY ON THE USE OF VIRTUAL ASSISTANTS FOR MANDARIN CHINESE INSTRUCTION - Astutiningtyas, Dessy; Rosyida, Desy Anindia (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
This paper discusses artificial intelligence-powered virtual assistants in the teaching of Mandarin as a second language at elementary level; they are analyzed with respect to their influence on learners’ linguistic knack, and cultural appreciation. The study adopts a qualitative research design using methods such as observation, interview and survey that will help examine how these AI tools facilitate learning processes and enhance interest through an ongoing form of learning that seeks to achieve thorough context-based cultural understanding. Results instructed us about major improvements realized in both language acquisition and cultural awareness; this research also raised a concern regarding the potential dangers resulting from excessive reliance on AI technologies in educational spheres. Therefore, this research advocates for use of artificial intelligence based devices that complement conventional teaching techniques so as to offer language instruction comprehensively without leaving out any aspect of the target culture.